SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) SMK KOMPUTAMA JERUKLEGI BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Muh Sofi'i; Wika Purbasari; Joko Purnomo (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2019)
Education has an important role in the success of national development. The government has established a 9-year compulsory education program (SD-SLTA). In order to reduce the unemployment rate the government is also encouraging the growth of Vocational Schools (SMK). At present there are many SMK that are growing, including SMK Komputama Jeruk Legi. Currently prospective student recruitment at SMK Komputama is still done manually, with increasingly rapid information technology development and also research related to the development of Student Reception Information System including Eviani and Zein, so in this study the design of Reception Information Systems Students in WEB-based Komputama Vocational School use CodeIgniter frmework using mySQL as DMBS. The product that has been made has been tested for product performance using the black box method, as well as the usability test using the usability test, the conclusion is that the Information System for Student Acceptance at Komputama Vocational School can be received and provides benefits. This recommendation was obtained from the results of the usability test on 100 respondents consisting of elements of teachers, students and the community.